Newly formed cystic lesions for the development of pneumomediastinum in Pneumocystis jirovecii pneumonia - Yoon Sung; Kwon Yong; Kim Dong-Min; Cho Ju-Yeon; Lee Seung (BMC Infectious Diseases, 2009)
Abstract Background Pneumocystis jirovecii, formerly named Pneumocystis carinii, is one of the most common opportunistic infections in human immunodeficiency virus (HIV)-infected patients. Case presentations We encountered two cases of spontaneous pneumomediastinum with subcutaneous emphysema in HIV-infected patients being treated for Pneumocystis jirovecii pneumonia with trimethoprim/sulfamethoxazole. Conclusion Clinicians should be aware that cystic lesions and bronchiectasis can develop in spite of trimethoprim/sulfamethoxazole treatment for P. jirovecii pneumonia. The newly formed bronchiectasis and cyst formation that were noted in follow up high resolution computed tomography (HRCT) but were not visible on HRCT at admission could be risk factors for the development of pneumothorax or pneumomediastinum with subcutaneous emphysema in HIV-patients.